Reticulados hiperbólicos em espaços quocientes mergulhados isometricamente em espaços euclidianos - Rodrigues, Laís Bássame (2010)
In this work we present a study of Möbius transformation sand fuchsian groups as the basis for the development of the theory of some specific quotient spaces. In these quotient spaces we consider geometrically uniform hyperbolic lattices that will be isometrically embedded in the sphere S8 c R9